Effect of Silanized Microcrystalline Cellulose Incorporation on Physicomechanical Properties and Denture Base Adaptation of Heat-Cured Acrylic Material - Nareman Muhannad Zaidan; Mina Amer Kamal; Noor Sabah Noori (Academic Journal of Clinicians, 2024)
Background: Among various polymers, acrylic resin is the material of choice for removable dentures fabrication. Nevertheless, it has some drawbacks, such as poor impact strength, low hardness, water sorption, and dimensional change. Recently, natural plant fillers have been used to improve polymers properties. Objective: to evaluate the impact of adding silanized microcrystalline cellulose on: impact strength, surface hardness, surface roughness, wettability, water sorption and solubility, and denture base adaptation of heat-cured acrylic denture base material. Materials and methods: A study was conducted to select the appropriate percentages of silanized microcrystalline cellulose to be used in the main study. Accordingly, 1wt.% and 1.5wt.% of silanized microcrystalline cellulose were selected. A total of 180 samples were equipped and separated into six main collections according to the tests. Then, each group was additional divided into three different subgroups grounded on the proportion of microcrystalline cellulose (0wt.%, 1wt.%, 1.5wt.%). Furthermore, by using field emission scanning electron microscope we analyzed the fractured surfaces of all specimens. Results: FTIR analysis revealed that (3-aminopropyl) trimethoxysilane was chemically bonded to microcrystalline cellulose. A significant increase in surface hardness and contact angle values of wettability test and significant reduction in the surface roughness test between control group and both experimental groups, (P˂0.01). Impact strength test, was significantly increase for 1.5wt.% as compared to the control group (P˂0.01). In specimens containing 1.5wt.%, a significant reduction occurred in water sorption test and solubility(P˂0.01). For denture base adaptation, no significant increase was observed in the gap measurement in the midline region between the cast and denture base for both experimental groups as compared to the control (P˃0.05). Conclusion: The addition of silanized microcrystalline cellulose to heat-cured acrylic can significantly improve its mechanical and physical characteristics. It reduces the acrylic wettability with the artificial saliva and leads to a non-significant increase of gap measurement in the midline region.